The Influence of Social Entrepreneurial Orientation on Students' Social Entrepreneurial Intention Mediated by Attitude toward Prosocial Behavior - Jatiwiwaha, Marcellino Priyana; Hitipeuw, Imanuel; Hanurawan, Fattah; Darman, Andrianus; Jatiperwira, Stefan Yudana (Universitas Ciputra Surabaya, 2026)
This study aims to examine the influence of social entrepreneurial orientation on social entrepreneurial intention among college students with attitude toward prosocial behavior as a mediator. This topic is chosen based on the development of the field of social entrepreneurship. The research method of this study is a cross-sectional design. The population is 3rd semester college students from the Faculty of Economics and Business of Universitas Negeri Surabaya. The sampling is done through simple random sampling, in which the sample size is 331. The analysis is done using PLS-SEM. Convergent validity and composite reliability of each construct is achieved. The results show that each hypothesis is confirmed based on the significance of path coefficients, which all of them are positive and significant. Based on the results, it is concluded that social entrepreneurial orientation influences social entrepreneurial intention mediated by attitude toward prosocial behavior.